Fuzzy Stability of Quadratic-cubic Functional Equations - Wang, Zhi Hua; Zhang, Wan Xiong (Acta mathematica Sinica. English series, 2011)
In this paper, the direct method and the fixed point alternative method are implemented to give Hyers-Uiam-Rassias stability of the functional equation 6f（x＋y）-6f（x-y）＋4f（3y）=3f（x＋2y）-3f（x-2y）＋9f（2y） in fuzzy Banach spaces. We can find the range of approximate solutions obtained using the direct method are less than those obtained by using the fixed point alternative method for the above and the functional equation.